EVIDENCE IN THE ANGOLAN PENAL PROCESS: PROHIBITIONS AND VALUATION (De Legibus - Law Journal, 2022)
The main objective of this article is to analyze the evidence, its valuation and prohibitions in the new Angolan criminal procedure code. The Angolan criminal process has undergone successive reforms since Angola became an independent state on November 11, 1975.Since that date, several separate procedural laws have been passed that regulated and adapted the Angolan criminal process in accordance with social circumstantialism.In this sense, one of the most recent reforms that the legislator introduced in the Angolan legal order, was the approval of the new penal procedural code on November 11, 2020 “Known as the code of independence or even, the first code of the post-independence was” thus consolidating the sovereignty of the Angolan State.However, with the theme that we undertake to discuss, we will try to solve several questions that we set out in the course of this research, highlighting the following: to what extent can evidence produced in the course of the investigation, the prosecution or even the trial be considered legality? Can the evidence considered prohibited be validated under the new Angolan criminal procedure code?In order to achieve these aspirations, we use the inductive method with a predominance of the bibliographic review technique, especially in the doctrinal analysis of the various positions that address the subject.
Keywords: evidence, valuation, prohibitions, Angolan criminal process; evidence; valuation; prohibitions; Angolan Criminal Process